The Criminal Responsibility or Sending Fictive Packages with Cash on Delivery Payment Method to Victims - Putra, Daffa Virgianto; Wahyuningsih, Yuli Yuliana (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
This study aims to analyze the Causal Factors and Legal Handling Mechanisms in cases of sending fictitious packages with the Cash on Delivery payment method, with reference to Law No. Article 378 of the Criminal Code concerning fraud, Law No. 19 of 2016 concerning Information and Electronic Transactions (UU ITE), and Law No. 27 of 2022 concerning Personal Data Protection (UU PDP).With the development of the era and technological advances, the phenomenon of fraud through sending fake packages with the Cash on Delivery payment method has become one form of crime that is increasingly rampant in various regions. This modus operandi is carried out by the perpetrator by sending goods that were never ordered by the victim. Although there are related regulations, the sending of fake packages continues to occur. This study uses a normative juridical method that analyzes theories, concepts, legal principles, and relevant regulations. The findings of this study conclude that criminals exploit weaknesses in the system, such as personal data leaks, minimal identity verification, and lack of digital literacy among consumers in purchasing goods online, therefore Handling this phenomenon requires collaboration between e-commerce parties, consumers, and law enforcement officers.